A New Scale for Measuring Reward Responsiveness - Van Den Berg, Ivo; Franken, Ingmar H.; Muris, Peter (Frontiers in Psychology, 2010)
Several psychological theories assume that there are two basic brain mechanisms that guide behavior: an avoidance or inhibition system, which is responsive to signals of punishment, and an approach or activation system, which is sensitive to signals of reward. Several self-report scales have been developed to assess the sensitivity to punishment and reward, and these instruments have been shown to be useful in research on personality, psychopathology, and underlying biological substrates. However, it is also true that in particular scales for measuring reward responsiveness suffer from various inadequacies. Therefore, a new Reward Responsiveness (RR) scale was developed and subjected to an extensive psychometric evaluation. The results show that this scale measures a single factor, reward responsiveness that is clearly independent of punishment sensitivity. Further, the data indicated that the internal consistency, convergent validity, discriminant validity, test-retest reliability, and predictive properties of the new scale were all adequate. It can be concluded that the RR scale is a psychometrically sound instrument that may be useful for researchers with interest in the personality construct of reward responsiveness.